Laser Additive Manufacturing: Design, Materials, Processes and Applications, 2nd Edition (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Laser-based additive manufacturing (LAM) represents one of the most forward-thinking transformations in how we conceive, design, and bring to life engineered solutions. By fusing digital design with material layering processes, LAM transcends the limitations of traditional subtractive manufacturing and equal material manufacturing, enabling the realization of material–micro/macrostructure–performance integration previously considered unattainable. Building on the work in the first edition and sincere cooperation with the Guest Editors, the second edition will continue to concentrate on laser additive manufacturing, including macro- to micro-scale additive manufacturing with lasers, including structure design/material design, fabrication, modeling, and simulation; in situ characterization of additive manufacturing processes; and ex situ material characterization and performances, with an overview of various applications in aerospace, biomedicine, optics, transportation, energy, etc. This Special Issue featured a diverse array of topics, publishing a total of 12 contributions (1 editorial, 1 review paper, and 10 original research papers), with over 17,000 views as of 15 July 2024. After the high-quality reviewing process, four articles were selected as Editor’s Choice.